The Clinical Characteristics, Neurobiology, and Treatment Options for Trichotillomania - Aldona, Wenty Septa (HM Publisher, 2023)
Trichotillomania is characterized by the compulsive act of pulling one's own hair, leading to hair loss and potentially causing functional impairment. Trichotillomania, a psychiatric disorder characterized by the compulsive need to pull out one's own hair, has been documented in the medical literature since the 19th century. Based on prevalence surveys, trichotillomania exhibits a notable presence throughout the population, with point prevalence estimates ranging from 0.5 to 2.0 percent. Trichotillomania, as delineated in the Diagnostic and Statistical Manual of Mental Disorders-5, is categorized as an obsessive-compulsive disorder (OCD); nonetheless, it exhibits notable distinctions from OCD across various dimensions. For instance, the use of habit reversal therapy and the administration of drugs like n-acetylcysteine or olanzapine are common ways to treat trichotillomania. It is important to note that these treatment approaches are not typically employed for the treatment of obsessive-compulsive disorder (OCD). In contrast, it appears that specific first-line medications for obsessive-compulsive disorder (such as selective serotonin reuptake inhibitors) do not demonstrate efficacy in treating trichotillomania. This article provides an overview of the existing body of knowledge pertaining to trichotillomania, a psychiatric disorder characterized by compulsive hair pulling. It also examines the available empirical evidence that supports various treatment approaches for this condition.